Lorenzo Ghiberti. - Krautheimer, Richard, 1897-1994 (Princeton University Press, 2019)
Volume 2 of 2. Lorenzo Ghiberti, sculptor and towering figure of the Renaissance, was the creator of the celebrated Bronze Doors of the Baptistery at Florence, a work that occupied him for twenty years and became known (at Michelangelo's suggestion, according to tradition) as the Doors of Paradise. Here Richard Krautheimer takes what Charles S. Seymour, Jr., describes as "a fascinating journey into the mind, career, and inventiveness of one of the indisputably outstanding sculptors of all the Western tradition." This one-volume edition includes an extensive new preface and bibliography by the author.Richard Krautheimer, Professor Emeritus of the Institute of Fine Arts at New York University, currently lives in Rome. He is the author of numerous works, including the Pelican Early Christian and Byzantine Architecture and Rome: Profile of a City, 312-1308 (Princeton).Princeton Monographs in Art and Archaeology, 31.Originally published in 1983.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Keywords: Ghiberti, Lorenzo, -- 1378-1455.; Ghiberti, Lorenzo, -- 1378-1455; Sculpture, Italian.; Sculpture italienne.; ART / General.; Sculpture, Italian